Solution of System of Volterra Integral Equations Using the Complex Sadiq Emad Eman Integral Transform - T., Ezra E.; J., Ankale H.; Y., Hali I. (Darul Yasin Al Sys, 2025)
Various analytical methods have been developed for solving systems of Volterra integral equations of both the first and second kind. In this study, we adopt and apply the complex Sadiq Eman Emad (SEE) integral transform as a novel approach for obtaining solutions to such systems. The complex SEE transform provides an effective framework for simplifying and solving integral equations through the use of operational techniques. This research explores the theoretical formulation of the transform, its properties including convolution and inverse operations and demonstrates its application through illustrative examples. The results confirm that the complex SEE integral transform offers a practical and efficient alternative for solving systems of Volterra integral equations, highlighting its potential for broader use in mathematical and engineering problems involving integral operators.